Uncooled resonant infrared detector based on aluminum nitride piezoelectric film through charge generations and lattice absorptions - Tan, Chuan Seng (2014)
This Letter demonstrates an aluminum nitride (AlN) based uncooled resonant infrared (IR) detector utilizing the photo-sensitive and piezoelectric properties of polycrystalline AlN. The AlN Lamb wave mode resonator is found responsive to IR illuminations by showing a decrease in the S 21 magnitude instead of a resonant frequency shift. A −0.08 dB shift of S 21 magnitude was observed for an IR incident power of 647 nW, which translates to a responsivity of 124 kdB/W. Photoresponse is proposed for the IR sensing mechanism through additional charge carriers generation rather than thermal effects.